Heat Stress Reduces Sperm Motility via Activation of Glycogen Synthase Kinase-3α and Inhibition of Mitochondrial Protein Import - Gong, Yabin; Guo, Huiduo; Zhang, Zhilong; Zhou, Hao; Zhao, Ruqian; He, Bin (Frontiers in Physiology, 2017)
The adverse effects of high environmental temperature exposure on animal reproductive functions have been concerned for many decades. However, the molecular basis of heat stress (HS)-induced decrease of sperm motility has not been entirely elucidated. We hypothesized that the deteriorate effects of HS may be mediated by damage of mitochondrial function and ATP synthesis. To test this hypothesis, we use mature boar sperm as model to explore the impacts of HS on mitochondrial function and sperm motility. A 6 h exposure to 42°C (HS) induced significant decrease in sperm progressive motility. Concurrently, HS induced mitochondrial dysfunction that is indicated by decreased of membrane potential, respiratory chain complex I and IV activities and adenosine triphosphate (ATP) contents. Exogenous ATP abolished this effect suggesting that reduced of ATP synthesis is the committed step in HS-induced reduction of sperm motility. At the molecular level, the mitochondrial protein contents were significantly decreased in HS sperm. Notably, the cytochrome c oxidase subunit 4, which was synthesized in cytoplasm and translocated into mitochondria, was significantly lower in mitochondria of HS sperm. Glycogen synthase kinase-3α (GSK3α), a negative regulator of sperm motility that is inactivated by Ser21 phosphorylation, was dephosphorylated after HS. The GSK3α inhibitor CHIR99021 was able to abolish the effects of HS on sperm and their mitochondria. Taken together, our results demonstrate that HS affects sperm motility through downregulation of mitochondrial activity and ATP synthesis yield, which involves dephosphorylation of GSK3α and interference of mitochondrial remodeling.